Personnel Expenditure Efficiency as an Impact of Public Service Quality in Teacher Requirements Planning - Fahrani, Novi Savarianti; Anisah, Azmi Listya; Syah, Ardy Firman; Ma’rifah, Diana (KnE Social Sciences, 2022)
In carrying out human resources planning, accurate calculations are needed so that the personnel expenditure burden is not too high in the regional revenue and expenditure budget (APBD). The current calculation of employee needs is based on the needs of teachers in each school, but it does not look at the community served, so the burden of personnel spending is very high. Elementary school teachers represent a high proportion of the personnel expenditure burden in the APBD. The aim of this study was to change the calculation of the need for elementary school teachers according to the concept of public service quality. This involved calculating the number of children aged 7-12 years as the community being served, the ideal number of students in one class, and the number of elementary school teachers who are associated with the average annual income of personnel. Quantitative methods were used with a descriptive analysis approach. This research was conducted from January to August 2021. The results indicated that using the concept of public service quality for these calculations can increase the efficiency of the budget in the APBD. Keywords: hr planning, calculation of elementary school teacher needs, public service quality, personnel expenditure, APBD